Systemic vasculitis and the gut. Issue 1 (January 2017) - Hatemi, Ibrahim; Hatemi, Gulen; Çelik, Aykut F.
Abstract : Purpose of review: Gastrointestinal system can be involved in primary and secondary vasculitides. The recent data regarding the pathophysiology, clinical findings, diagnosis, management, and outcome of gastrointestinal involvement in different types of vasculitis are reviewed. Recent findings: Diagnosis of gastrointestinal vasculitis may be difficult and relies mostly on imaging, because biopsy samples are hard to obtain and superficial mucosal biopsies have a low yield. There are conflicting reports on the association of antineutrophilic cytoplasmic antibodies (ANCA) type with the frequency of gastrointestinal involvement in ANCA-associated vasculitis. Pancreatitis is a rare but serious complication of ANCA-associated vasculitis. Terminal ileitis may be observed in immunoglobulin A vasculitis and can be hard to distinguish from Crohn's disease. High fecal calprotectin levels can indicate active gastrointestinal involvement in both immunoglobulin A vasculitis and Behçet's syndrome. Refractory gastrointestinal involvement in Behçet's syndrome can be treated with thalidomide and/or TNF-α antagonists. The outcome of mesenteric vasculitis in systemic lupus erythematosus can be improved with high-dose glucocorticoids and cyclophosphamide or rituximab. Summary: Gastrointestinal system can be commonly involved in immunoglobulin A vasculitis, ANCA-associated vasculitis, polyarteritis nodosa, and Behçet's syndrome and can be an important cause of morbidity and mortality. Treatment depends on the type of vasculitis and is usually with high-dose corticosteroids and immunosuppressives.